A Receiver-Initiated MAC Protocol for Wireless Sensor Networks Based on Tree Topology. (1st October 2015) - Park, Inhye; Yi, Joonhwan; Lee, Hyungkeun
Abstract : This paper proposes receiver-initiated X-MAC with tree topology (TRIX-MAC), an improved energy-efficient MAC protocol based on an asynchronous duty cycling for wireless sensor networks with tree topology. TRIX-MAC improves energy efficiency through utilizing short preambles and adopting the receiver-initiated approach that minimizes sender nodes' energy consumption by enabling transmitters to predict receiver nodes' wake-up times and reduces receiver nodes' energy consumption by decreasing the number of control frames. In many sensor network applications, the data flow from source nodes to a sink forms a unidirectional tree. A property of tree topology, the parent-child relation, is also exploited to reduce the likelihood of collisions between frames sent by children nodes. We use the network simulator, ns-2, to evaluate TRIX-MAC's performance. Compared to the prior asynchronous duty cycling approaches of X-MAC, RIX-MAC, and PW-MAC, the proposed protocol shows better performance in terms of throughput, energy efficiency, and end-to-end delay.